Who Advances Nursing Science in Practice Settings and How?. (October 2021) - Granger, Bradi B.; Johnson, Karen; Norful, Allison; Westlake, Cheryl; Tracy, Mary Fran
Abstract : Nurse scientist (NS) roles in clinical practice settings are key components of The Future of Nursing and ANCC Magnet ® recognition. Despite increased opportunities for NS roles, leveraging these roles to advance nursing science remains at an early stage. We describe opportunities and challenges for NSs in clinical practice settings, highlighting the value of a strong partnership with chief nurse officers as critical for the success of NSs and outcomes associated with these roles.